Chapter: 'A Value Model for MOOCs' from book: Adaptive and Adaptable Learning: 11th European Conference on Technology Enhanced Learning, EC-TEL 2016, Lyon, France, September 13-16, 2016, Proceedings - Yishay Mor (Lecture Notes in Computer Science, 2016)
Massive Open Online Courses (MOOCs) are changing the educational field, challenging traditional institutional strategies and recognition schemes and opening up new opportunities for learners and educators both from within and outside formal education. However, while the potential benefits and risks of the MOOCs have been discussed by scientists and policy makers, the corresponding empirical data is scarce. What's more, the evidence that is available is usually restricted to a single course or single provider. MOOCKnowledge (http://moocknowledge.eu/), funded by the European Commission's Institute for Prospective Technological Studies (IPTS), aims to facilitate a shared understanding of the value and efficacy of MOOCs by developing a set of analysis tools and applying them to a wide range of MOOCs. The most powerful outcome of the project would be the possibility to correlate different dimensions of MOOC production, execution, and learners experience. For example, identifying links between financial investment, learning design, and learner outcomes. To do this, we must first develop a conceptual model of the factors which determine or contribute to the value of a MOOC.